Peran Penyuluhan dalam Meningkatkan Produksi Susu Peternak Anggota Koperasi Peternakan Bandung Selatan (KPBS) Pangalengan - Yunasaf, Unang; Sulistyati, Marina; Nurlina, Lilis; Alim, Syahirul; Mauludi, Moch. Ali (Universitas Galuh, 2025)
The study occurred at the South Bandung Livestock Cooperative (KPBS) Pangalengan, Bandung Regency, West Java. The study aimed to find out how extension services contribute to boosting milk output among the member farmers of KPBS Pangalengan. The study used a descriptive approach involving all extension workers assigned to the KPBS Pangalengan extension sub-unit, totaling 7 people. The results of the research showed that Extension plays an important role in increasing the milk production of dairy farmers who are members of KPBS Pangalengan. The role that has been carried out by extension is shown by programs or activities that include: (1) Group assistance and cage checklists, (2) Increasing insight and skills in managing dairy cattle, (3) Providing materials for developing family businesses, and finances, (4) Making posters or leaflets, (5) Listening to radio broadcasts together, (6) Nail cutting services, (7) Training for extension workers, and (8) Provision of milking sanitation facilities. Milk production achieved by farmers showed an increase, an average of 3.14 percent in the last two months, which was originally 59,086 kg in April 2024, increasing to 60,638.28 kg in June 2024.